Limit theorems for age-structured populations - Oelschläger, Karl (The annals of probability, 1990)
We study populations consisting of individuals whose birth and death rates depend on both their age and the age-structure of the whole population. In particular, as the population size tends to infinity, we derive a law of large numbers and a central limit theorem for the empirical processes.